Dynamic analysis of single-degree-of-freedom systems (DYANAS): A graphical user interface for OpenSees. (15th December 2018) - Baltzopoulos, Georgios; Baraschino, Roberto; Iervolino, Iunio; Vamvatsikos, Dimitrios
Highlights: Presentation of an open-source, graphical user interface for OpenSees. The software performs dynamic analysis of yielding single-degree-of-freedom systems subjected to accelerograms. Incremental dynamic, multi-stripe and cloud analysis are supported. Post-processing routines render the software a tool for performance-based earthquake engineering. Examples of probabilistic seismic demand analysis are provided. Abstract: Non-linear dynamic response of SDOF systems enjoys widespread application in earthquake engineering, sometimes as a testing ground for cumbersome analytical procedures, but often as a direct proxy of first-mode-dominated structures, within the family of simplified, pushover-based methods for seismic structural assessment and/or design. This article presents DYANAS, a MATHWORKS-MATLAB ® -based graphical user interface that uses the OpenSees finite element platform to perform nonlinear dynamic analysis of single-degree-of-freedom (SDOF) oscillators. The scope of this open-source, freely distributed software is to serve as a tool for earthquake engineering research. The main advantages offered by the DYANAS interface are ease in the definition of the required analysis parameters and corresponding seismic input, efficient execution of the analyses themselves and availability of a suite of convenient, in-built post-processing tools for the management and organization of the structural responses. The types of dynamic analysis frameworks supported are incremental, multiple-stripe and cloud. Simultaneous consideration of pairs of uncoupled dynamic systems gives the possibility for intensity measures to refer to bidirectional ground motion. In the paper, an outline of the types of dynamic analysis frameworks typically used in performance-based earthquake engineering is provided, followed by a detailed description of the software and its capabilities, that include an array of post-processing tools. In order to properly place this software tool within its natural performance-based earthquake engineering habitat, some example applications are provided at the end of the paper.